Strategi Pengembangan Sumber Daya Manusia di Lembaga Pendidikan (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out the strategies applied by educational institutions in human resource development. This study uses a qualitative approach with a literature study method. Method. The main source of data for this study is the results of previous research published through various scientific journals and indexed on the database on Google Scholar. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that human resources are the most important asset in every organization, playing a vital role in achieving goals and long-term success. The fundamental element that determines the quality of education and student development, including teachers, administrative staff, and other supporters who work together to create a conducive and inspiring learning environment is the human resources in schools. Human resource development involves various activities, such as training, education, career development, and continuous learning programs. By focusing on human resource development, organizations can increase employee productivity, innovation, and referrals, all of which contribute to the achievement of strategic goals and competitive advantage